PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS PESERTA DIDIK KELAS VIII-1 SMP NEGERI 20 PEKANBARU - Ike Nurhidayah Judtianti; Armis Armis; Maimunah Maimunah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The inability of students to answer questions both exercise and test shows that there is still a lack of understanding of the learning material given by the teacher. This research aims to improve the learning process and the student’s mathematical understanding skill by discovery learning model. The type of this research is Classroom Action Research with two cycles. The subjects of this research were students of class VIII-1 SMP Negeri 20 Pekanbaru. This study was conducted in the first semester of academic year 2018/2019. The research instruments used are mathematical learning instruments (Syllabus, Lesson Plans, and Student Worksheet) and instruments for collecting data (Observation Sheets and Mathematical-Understanding Tests). The observation sheets were used to find out the data of students and teacher activity during learning process which would analyzed quantitatively and qualitatively. Mathematical understanding test were used to collect the student’s mathematical understanding skill outcomes which would analyzed quantitatively. The results of learning process had happened improvement from implementation on cycle I to cycle II. Average score for implementation of teacher’s activities for cycle I is 94.61 improved to 100 in cycle II. Average score for implementation of student’s activities for cycle I is 90.67 improved to 100 in cycle II. Result of the test indicates that the student’s learning achievement for the first is 43.33 improved in cycle I to 64.38 and improved to 81.88 in cycle II. Based on the result above, it can be concluded that the implementation of discovery learning model approach can improve the learning process and the student’s mathematical understanding skill outcomes at class VIII-1 SMP Negeri 20 Pekanbaru.Key Words: mathematical understanding skill, discovery learning, classroom action research